(untitled) (Eurasian Medical Research Periodical, 2022)
Pulmonary embolism (PE) is the third most common cause of cardiovascular death. When PE burden is severe, right ventricular failure usually occurs within the first few hours, so it should be diagnosed rapidly to identify patients who could benefit from fibrinolytic therapy. Aim: Detection and assessment of CT pulmonary angiographic findings in patients with acute pulmonary embolism that can predict the short term sequels